Concurrent müllerianosis of the urinary bladder and the umbilicus presenting with umbilical bleeding: a rare case report and review of the literature - Syu Jhang; Marcelo Chen; Li-Chen Chen (BMC, 2020)
Abstract Background Müllerianosis is a very rare neoplasm composed of two or three Müllerian derived tissues (endosalpinx, endometrium and endocervix). We report the first case of concurrent müllerianosis of the urinary bladder and the umbilicus presenting with umbilical bleeding. Case presentation A 43-year-old Asian premesopausal female, gravida 1, para 1, presented with intermittent umbilical bleeding. An umbilical nodule and a bladder tumor on the posterior wall of the urinary bladder were identified. She underwent transurethral resection of the bladder tumor and excision of the umbilical nodule successively. Diagnosis of müllerianosis was confirmed by the histological and immunological features. No tumor recurrence was noted at 6 months of follow-up. Conclusions Müllerianosis is extremely rare and mainly reported in the urinary bladder, and generally affects women of reproductive age. Despite the common presentations of müllerianosis of the urinary bladder including irritative voiding symptoms, abdominal/pelvic pain and gross hematuria, our rare case had no symptom except umbilical bleeding. The possibility of concurrent bladder müllerianosis should be considered when müllerianosis is found at other location. We suggest a surgical intervention to establish the correct pathological diagnosis because it is essential to exclude malignant neoplasms of the urinary bladder. The majority of patients have a favorable prognosis.